One-Step Electrochemical Fabrication of Reduced Graphene Oxide/Gold Nanoparticles Nanocomposite-Modified Electrode for Simultaneous Detection of Dopamine, Ascorbic Acid, and Uric Acid - Chang-Seuk Lee (Nanomaterials, 2017)
Here, we introduce the preparation of the hybrid nanocomposite-modified electrode consisting of reduced graphene oxide (RGO) and gold nanoparticles (AuNPs) using the one-step electrochemical method, allowing for the simultaneous and individual detection of dopamine (DA), ascorbic acid (AA), and uric acid (UA). RGO/AuNPs nanocomposite was formed on a glassy carbon electrode by the co-reduction of GO and Au3+ using the potentiodynamic method. The RGO/AuNPs nanocomposite-modified electrode was produced by subjecting a mixed solution of GO and Au3+ to cyclic sweeping from −1.5 V to 0.8 V (vs. Ag/AgCl) at a scan rate 10 mV/s for 3 cycles. The modified electrode was characterized by scanning electron microscopy, Raman spectroscopy, contact angle measurement, electrochemical impedance spectroscopy, and cyclic voltammetry. Voltammetry results confirm that the RGO/AuNPs nanocomposite-modified electrode has high catalytic activity and good resolution for the detection of DA, AA, and UA. The RGO/AuNPs nanocomposite-modified electrode exhibits stable amperometric responses for DA, AA, and UA, respectively, and its detection limits were estimated to be 0.14, 9.5, and 25 μM. The modified electrode shows high selectivity towards the determination of DA, AA, or UA in the presence of potentially active bioelements. In addition, the resulting sensor exhibits many advantages such as fast amperometric response, excellent operational stability, and appropriate practicality.